Fish species-specific TRIM gene FTRCA1 negatively regulates interferon response through attenuating IRF7 transcription. Issue 90 (July 2019) - Wu, Min; Dan, Cheng; Gui, Jian-Fang; Zhang, Yi-Bing
Abstract: In mammals and fish, emerging evidence highlights that TRIM family members play important roles in the interferon (IFN) antiviral immune response. Fish TRIM family has undergone an unprecedented expansion leading to generation of finTRIM subfamily, which is exclusively specific to fish. Our recent results have shown that FTRCA1 (finTRIM C. auratus 1) is likely a fish species-specific finTRIM member in crucian carp C. auratus and acts as a negative modulator to downregulate fish IFN response by autophage-lysosomal degradation of protein kinase TBK1. In the present study, we found that FTRCA1 also impedes the activation of crucian carp IFN promoter by IRF7 but not by IRF3. Mechanistically, FTRCA1 attenuates IRF7 transcription levels likely due to enhanced decay of IRF7 mRNA, leading to reduced IRF7 protein levels and subsequently reduced fish IFN expression. E3 ligase activity is required for FTRCA1 to negatively regulate IRF7-mediated IFN response, because ligase-inactive mutants and the RING-deleted mutant of FTRCA1 lose the ability to block the activation of crucian carp IFN promoter by IRF7. These results together indicate that FTRCA1 is a multifaceted modulator to target different signaling factors for shaping fish IFN response in crucian carp. Highlights: FTRCA1 impedes the activation of crucian carp IFN promoter by IRF7. FTRCA1 attenuates IRF7 transcription levels likely due to enhanced decay of IRF7 mRNA. E3 ligase activity is required for FTRCA1 to negatively regulate IRF7-mediated IFN response.